Association of chronic plaque psoriasis and severe periodontitis: a hospital based case‐control study. (15th June 2012) - Lazaridou, E.; Tsikrikoni, A.; Fotiadou, C.; Kyrmanidou, E.; Vakirlis, E.; Giannopoulou, C.; Apalla, Z.; Ioannides, D.
Abstract: Background  Both chronic plaque psoriasis and periodontitis have an increasing prevalence worldwide and have been associated with the metabolic syndrome; however limited information is available on their association. Objective  To evaluate the possible association of severe periodontitis and chronic plaque psoriasis. Methods  This was a hospital based case‐control study. Chronic plaque psoriasis patients and age‐ and gender‐matched controls have been recruited. Baseline demographic data have been recorded. To explore correlations between different dichotomous variables the Sperman Rho correlation coefficient was used. Correlations were further explored non‐parametrically and univariate and multivariate logistic regression was utilized after adjustment for the effect of confounders. Results  During the study enrolment period 100 patients with CPP and 100 age‐ and gender‐matched controls were included in this study. Mean age for both groups was 57.2 ± 5.3 years. 43% of patients and controls were males. Significant correlations where noted between psoriasis and 1) periodontitis (rho = 0.219, P  = 0.02) and 2) metabolic syndrome (rho = 0.191, P  = 0.07) using Spearman's Rho correlation co‐efficient. Univariate logistic regression reported significant relations between psoriasis and periodontitis (OR = 3.329, 95%CI: 1.513–7.324, P  = 0.003) and psoriasis and metabolic syndrome (OR = 2.293, 95%CI: 1.250–4.207, P  = 0.007). On the contrary, a non‐significant relation between psoriasis and active smoking status was detected (OR = 1.041, 95%CI: 0.597–1.817, P  = 0.887). In a multivariate analysis model we found a significant correlation of psoriasis and periodontitis when controlled for the presence of metabolic syndrome (OR: 2.486, 95%CI: 1.002–5.842, P  = 0.049). Conclusion  Periodontitis may be associated with psoriasis but further studies are required to elucidate their relationship in the context of the biologic plausibility.